2021
DOI: 10.3390/molecules26175273
|View full text |Cite
|
Sign up to set email alerts
|

Chromone Derivatives with α-Glucosidase Inhibitory Activity from the Marine Fungus Penicillium thomii Maire

Abstract: The fungal strain YPGA3 was isolated from the sediments of the Yap Trench and identified as Penicillium thomii. Eight new chromone derivatives, named penithochromones M−T (1–8), along with two known analogues, 9 and 10, were isolated from the strain. The structures were established by detailed analyses of the spectroscopic data. The absolute configuration of the only chiral center in compound 1 was tentatively determined by comparing the experimental and the calculated specific rotations. Compounds 7 and 8 rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Han and co-workers screened out for bioactive molecules from deep-sea fungus, the fungal strain Penicillium thomii YPGA3, isolated from the sediments at a depth of 4500 m in the Yap Trench. 84 The 1 H NMR spectrum and HPLC-DAD fingerprint of the EtOAc extract of this strain suggested the presence of chromone derivatives, and as a result, eight new chromone derivatives, namely penithochromones M−T (134− 141, Figure 16), along with two known analogs, were isolated. These compounds were evaluated as α-glucosidase inhibitors, and the results showed that compounds 139, 140, and 141 exhibited comparable effects as the positive control acarbose (1.33 mM) with IC 50 values of 842, 917, and 1017 μM, respectively.…”
Section: Acsmentioning
confidence: 96%
See 3 more Smart Citations
“…Han and co-workers screened out for bioactive molecules from deep-sea fungus, the fungal strain Penicillium thomii YPGA3, isolated from the sediments at a depth of 4500 m in the Yap Trench. 84 The 1 H NMR spectrum and HPLC-DAD fingerprint of the EtOAc extract of this strain suggested the presence of chromone derivatives, and as a result, eight new chromone derivatives, namely penithochromones M−T (134− 141, Figure 16), along with two known analogs, were isolated. These compounds were evaluated as α-glucosidase inhibitors, and the results showed that compounds 139, 140, and 141 exhibited comparable effects as the positive control acarbose (1.33 mM) with IC 50 values of 842, 917, and 1017 μM, respectively.…”
Section: Acsmentioning
confidence: 96%
“…Compounds 134 – 141 were also assessed for their antioxidant activity, at the initial concentration of 1 mM, using a DPPH radical assay. The data found revealed that all tested compounds exhibit very weak inhibition (less than 50%) . More recently, additional research by this group on the same fungal strain led to the isolation of three new chromone analogs, named penithochromones U–W ( 142 – 144 , Figure ).…”
Section: Chromones and Chromanones From Natural Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…219 Deep-sea sediment and sediment-derived Penicillium strains have been the source of numerous metabolites. Deep-sea-derived compounds include chromone derivatives 597–604 , 220 meroterpenoids 605–607 , 221 p -terphenyls 608–610 , 222 drimane sesquiterpenes 611 and 612 , and polyketides 613–618 . 223 Sesquiterpene lactone 619 , 224 resorcinol-long chain fatty acid derivatives 620–624 , oxygenated polyene 625 , pyridinone derivative 626 , 225 and polyhydroxoxanthones 627–631 , 226 were also isolated from sediment-derived Penicillium strains.…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%